2015
DOI: 10.4049/jimmunol.1502269
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Decreased T Follicular Regulatory Cell/T Follicular Helper Cell (TFH) in Simian Immunodeficiency Virus–Infected Rhesus Macaques May Contribute to Accumulation of TFH in Chronic Infection

Abstract: This information is current as Infection in Chronic FH to Accumulation of T Infected Rhesus Macaques May Contribute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Frequencies of highly functional memory T FH cells in the blood are associated with bnAb development in HIV-infected humans (Locci et al, 2013;Moody et al, 2016). GC-T FH cells are also positively correlated with nAb development in simian immunodeficiency virus positive (SIV + ) RMs and SHIV + RMs (Chowdhury et al, 2015;Petrovas et al, 2012;Yamamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Frequencies of highly functional memory T FH cells in the blood are associated with bnAb development in HIV-infected humans (Locci et al, 2013;Moody et al, 2016). GC-T FH cells are also positively correlated with nAb development in simian immunodeficiency virus positive (SIV + ) RMs and SHIV + RMs (Chowdhury et al, 2015;Petrovas et al, 2012;Yamamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also in mice, it was demonstrated that excessive numbers of T FH are correlated with impaired affinity maturation, and restoring a balanced ratio of T FH to T FR allows for generation of highly mutated, high avidity antibodies (85). Recent studies in rhesus macaques have shown that T FR frequencies in secondary lymphoid tissues are increased in chronically SIV-infected animals (48, 86), while another study found decreases in T FR during chronic infection (87). Reasons for discrepancies among these studies are not clear.…”
Section: Mechanisms That Underlie Tfh Dysfunctionmentioning
confidence: 98%
“…It is known that one of the main immunologic features of sarcoidosis is the influx of CD4 + T cells into the active sites of this disease. T FH cells are nonpolarized CD4 + T cells that express high levels of the chemokine receptor CXCR5; the homing exerted by its ligand CXCL13 chemokine allows follicular migration, where they are thought to act as a regulator of host humoral immune responses [19,23]. Infiltration of T FH into skin lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…That explains why T FH cells might play crucial roles in common autoimmune diseases; hence, they were reported as a potential biomarker in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) due to increased T FH cell numbers in those diseases [16,17]. On the other hand, decreased T FH cells were found in ankylosing spondylitis, hepatocellular carcinoma and chronic infections [18][19][20]. The features of T FH cells and their subsets in sarcoidosis patients have not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%